A nomogram predicting the risk of venous thromboembolism in patients following urologic surgeries - Mengchao Wei; Wenjie Yang; Yi Qiao; Lin Ma; Weifeng Xu; Jie Dong (Scientific Reports)
Abstract There are inconsistent results pertaining to risk factors for venous thromboembolism (VTE) in patients following urologic surgeries. We attempted to establish a visualization model to shed further light upon this topic. Consequently, a total of 436 patients who were tested for VTE following urologic surgeries were retrospectively enrolled. Least absolute shrinkage and selection operator method (LASSO) method was utilized to determine risk factors for VTE and a subsequent nomogram was constructed. The concordance index (C-index) and calibration curve were utilized to evaluate the nomogram. The results suggested that age, history of smoking, D-dimer levels on the first postoperative day, transfusion volume and body mass index (BMI) were identified as significant risk factors for VTE. The C-index of the nomogram composed of the five variables was 0.747 (95% CI 0.700–0.793) and the calibration plot demonstrated good performance. Therefore, the present nomogram could predict the risk of VTE following urologic surgeries.